Modulation of western North Pacific tropical cyclone decadal variability by the Victoria mode - Tao Wen; Jianping Li; Shifei Tu; Ruiqiang Ding; Quanjia Zhong; Xumin Li (Environmental Research Letters)
Intense tropical cyclones (TCs) in the southeastern western North Pacific (SE-WNP) significantly impact East Asian coastal nations. Decadal variability in TC genesis frequency (TCGF) has been linked to the Pacific decadal oscillation (PDO), a major sea surface temperature (SST) pattern in the North Pacific. However, based on extended observation records, we show that the decadal variability of SE-WNP TCGF is mainly driven by the Victoria mode (VM), a secondary but prominent SST pattern in the North Pacific. During the positive VM phase, the SE-WNP TCGF is more than usual due to the anomalous large-scale environmental fields induced by the VM-related central North Pacific SST anomalies; conversely, the SE-WNP TCGF is less during the negative VM phase. This highlights the crucial role of the VM in modulating TC activity, challenging the traditional view that the PDO is the dominant factor, with important implications for SE-WNP TC climate predictions.